The use of holmium-yttrium aluminum garnet laser as pit and fissure cleaner - Armasastra Bahar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: The prevention and management of pit and fissure caries has become relatively more important in recent times. There is a need for an effective preventive measure against pit and fissure caries. Purpose: The purpose of this study was to investigate the effect of laser beam as a cleaning method of pits and fissures. Methods: Ho-YAG laser which has a wavelength of 2.1 µm was used in this experiment. The specimens were extracted human teeth. The effect of three cleaning methods was examined comparatively by scoring the cleaned area of fissure, namely laser irradiation with Ho-YAG laser, chemico-mechanical with combination of 10% NaOCl and ultrasonic scaler and mechanical with ultrasonic scaler. Vertico-bucco-lingual serial ground sections of each tooth were observed under light microscopy. Scoring the depth of cleaned area was performed by comparing the depth of fissure. result: Progressive result was obtained on the cleaning effect of three methods laser irradiation methods which was the most effective compared to other methods but statistically was not significant. Cleaned area of laser irradiation method was 48.91%, chemico-mechanical method was 41.77% and mechanical method was 36.78%. Conclusion: Holmium -yttrium aluminum garner laser is a relatively new method for pit and fissure cleaning even though the effectivity is not yet maximal. More research is needed to maximize the use of this laser.